A Microtitre Plate Dilution Method for Minimum Killing Concentration Is Developed to Evaluate Metabolites-Enabled Killing of Bacteria by β-lactam Antibiotics - Tao, Jian-jun; Xiang, Juan-juan; Jiang, Ming; Kuang, Su-fang; Peng, Xuan-xian; Li, Hui (Frontiers in Molecular Biosciences, 2022)
Because yet few new antibiotics active against multidrug-resistant bacteria are being explored, compounds including metabolites that might help us tide over this crisis are greatly expected. Recently adopted method to evaluate the potentiation of metabolites is plate-counting test. However, the method is time-consuming, strenuous and unfeasible for a large scale of screening. Minimum inhibitory concentration (MIC) test by using a microtitre plate dilution method is convenient and economic for the large scale of identification, but it cannot be used to detect the potentiation. Here, the microtitre plate dilution method was modified to develop a novel test for evaluating metabolites that enable the killing of bacterial pathogens by antibiotics, designed as minimum killing concentration (MKC). To do this, bacterial number, incubation time, ionic strength of M9 medium, inosine concentration are optimized using Escherichia coli. Different from MIC test, which uses 5 × 104 colony forming unit (CFU) cells and performed in LB medium, MKC test needed 1 × 107 CFU - 2 × 107 CFU cells and was carried out in M9 medium. Moreover, MKC test was suitable for bactericidal antibiotics such as cephalosporins, penicillins and carbapenems and proportional to plate-counting test. The developed MKC test is feasible for different metabolites and clinically multidrug-resistant pathogens, and measurement of minimum bactericidal concentration (MBC). Therefore, the MKC test is developed to accelerate identification of compounds that promote antibiotic-mediated killing efficacy.